Pembangunan Kesejahteraan Sosial melalui Program Usaha Sosial Ekonomi Produktif Keluarga Miskin (USEP-KM) di Kota Yogyakarta. - , YERRYMIAZ SILVALEONDI .S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research about \"Social Welfare Development through Social Enterprise for Productive Economy of Poor Families (USEP-KM program) in the City of Yogyakarta\" took 4 (four) USEP-KM empowerment groups as an object of research. For location of the research, there are two groups aged less than 9 (nine) years who received ratings of bad and good/independent. Meanwhile, two other groups aged over 16 (sixteen) years who received ratings of bad and good/independent. Each of the two groups are from Jetis and Umbulharjo subdistricts. Based on two characteristic above, location of the research are USEP Bumijo I (old group and have good/independent rating), USEP Bumijo II (new group and have bad rating), USEP Warungboto (old group and have bad rating) and USEP Sorosutan II (new group and have good/independent rating) This research using descriptive qualitative research method. Primary data sources consisted of interviews, observations, field documentations and secondary data sources are program plan documents. Informant selection techniques using purposive sampling and snowball sampling. Informants in this research consisted of 32 (thirty two) peoples, with the selection of informants based on three categories of informants which are program planners, program implementers and the target of program. Data analysis will be performed with consisted of data collection, data reduction, compilation and analysis of data and making conclusions and suggestions In the program plan known that USEP-KM program more emphasis on social empowerment. The program works to improve WKBS (poor housewives) welfare by forming social functioning. So the concern among fellow members can help individual problems or group problems itself. USEP-KM group failure and success determined by quality and program management pattern. In implementation program there are several program implementers which are city level advisor and subdistrict level advisor, who do not understand their important role in the progress of the group. Differences in program implementation in each group causing diversity in USEP-KM groups achievements. Groups with high social functioning, providing convenience and inspiration for members, while the group with low functioning, causing business continuity members cannot develop properly. Members cannot find a solution to the problems in their business activities. The groups aged over 16 (sixteen) years, having problems in improving member roles in the group. The reason was misguided practices that have been applied in old USEP-KM groups for along time. While the groups aged less than 9 (nine) years, can more easily adapt to the USEP-KM system, despite had some constraints in the group development, currently they can apply innovations in organizing group activities.